Accounting Practices in the Barapan Kebo Custom in Sumbawa Regency - Lidya Meti Fiorentina; Lalu Takdir Jumaidi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Traditional accounting practices in the context of the Barapan Kebo tradition in Sumbawa Regency have not yet been widely researched. This research seeks to fill this gap in the literature by focusing on how buffalo breeders and traditional actors in this tradition record, measure costs and determine profits. Using an ethnographic approach, data was collected through observations and interviews for days in the field. The results show that the concept of profit and loss is not only seen from a material perspective, but is also influenced by spiritual beliefs and local beliefs. Even though financial recording practices tend to be informal, the importance of financial monitoring is still reflected through simple recording carried out by the executive committee. The emphasis on non-material aspects in assessing profits, such as happiness and gratitude, illustrates that spiritual cultural values play a key role in accounting practices in the Barapan Kebo tradition. Accounting is understood as financial management that is not only practical, but also closely connected to the cultural and spiritual values of society.